Basics of Electromagnetics and Transmission Lines - Reddy, G. Jagadeeswar. (Milton)
1 online resource (354 p.)
Keywords: This book provides a complete awareness on the subject EMTL with regards to both theoretical and practical aspects of the subject. Various concepts from fundamentals to advanced topics are presented and discussed adequately. The book's bottom-up approach ensures that students understand all the basic building blocks before the development of a real-life system. Numerical problems and day-to-day examples, practical situations that occur in industries & daily life are also presented. Please note: Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.